2013
DOI: 10.1111/apha.12138
|View full text |Cite
|
Sign up to set email alerts
|

Maternal chocolate and sucrose soft drink intake induces hepatic steatosis in rat offspring associated with altered lipid gene expression profile

Abstract: Our results suggest that supplementation of chocolate and soft drink during gestation and lactation contributes to early onset of hepatic steatosis associated with changes in hepatic gene expression and lipid handling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 49 publications
4
31
2
Order By: Relevance
“…*p < 0.05 versus oil treatment affect the prenatal differentiation of neurons in offspring and result in impaired ability for social interaction. Collectively, these observations agree with the previous findings that maternal factors, including health status and nutrition, can cause unfavorable outcomes in offspring (Leret et al 2009;Hussain et al 2013;Kjaergaard et al 2014;Pruis et al 2014a, b;Taylor et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…*p < 0.05 versus oil treatment affect the prenatal differentiation of neurons in offspring and result in impaired ability for social interaction. Collectively, these observations agree with the previous findings that maternal factors, including health status and nutrition, can cause unfavorable outcomes in offspring (Leret et al 2009;Hussain et al 2013;Kjaergaard et al 2014;Pruis et al 2014a, b;Taylor et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Whether these physiological changes, seen in offspring prenatally exposed to western diet, are induced by elevated dietary fat content per se or are instead due to a change in dietary fatty acid composition was not addressed in this experimental design. Murine models have consistently described lipid abnormalities in offspring exposed to a high-fat diet during early phases of development (Bruce et al 2009, Elahi et al 2009, Gregorio et al 2010, Oben et al 2010, Ashino et al 2012, Kjaergaard et al 2013, Kruse et al 2013, Mouralidarane et al 2013. We here compared western-type diet (moderate fat and cholesterol) to matched semisynthetic control diet.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, several groups have described that gestational energy-rich diets can programme hepatic steatosis or even non-alcoholic steatohepatitis (NASH) in the offspring in rodent models (Bruce et al 2009, Elahi et al 2009, Gregorio et al 2010, Oben et al 2010, Ashino et al 2012, Kjaergaard et al 2013, Mouralidarane et al 2013. Often, these studies compare rodent chow with different diets based on lard as the main fat source (35, 45 or 60%), sometimes combined with high fructose intake or condensed milk.…”
mentioning
confidence: 99%
“…Alterations in plasma levels of HF-diet-fed newborn were observed (Franco et al, 2012;Troina et al, 2010;Tsuduki et al, 2013), but the mechanism remains unclear and may involve placental effects (Sabri et al, 2014). Previous studies have shown different results (Guarda et al, 2014;Kjaergaard, Nilsson, Rosendal, Nielsen, & Raun, 2014), suggesting that maternal nutritional status during pregnancy and lactation influences the methylation of genes related to lipid metabolism in the offspring (Aagaard-Tillery et al, 2008;Jousse et al, 2011).…”
Section: Discussionmentioning
confidence: 99%